Central and peripheral line-associated bloodstream infections in Australian neonatal and paediatric intensive care units: findings from a comprehensive Victorian surveillance network, 2008–2016. Issue 1 (May 2018) - Worth, L.J.; Daley, A.J.; Spelman, T.; Bull, A.L.; Brett, J.A.; Richards, M.J.
Summary: Background: Healthcare-associated infections in neonatal and paediatric populations are associated with poorer outcomes and healthcare costs, and surveillance is a necessary component of prevention programmes. Aim: To evaluate burden of illness, aetiology, and time-trends for central and peripheral line-associated bloodstream infection (CLABSI and PLABSI) in Australian neonatal and paediatric intensive care units (ICUs) between July 1 st, 2008 and December 31 st, 2016. Methods: Using National Healthcare Safety Network methods, surveillance in neonatal and paediatric units was performed by hospitals participating in the Victorian Healthcare Associated Infection Surveillance System. Mixed effects Poisson regression was used to model infections over time. Findings: Overall, 82 paediatric CLABSI events were reported during 37, 125 CVC-days (2.21 per 1000 CVC-days), 203 neonatal CLABSI events were reported during 92, 169 CVC-days (2.20 per 1000 CVC-days), and 95 neonatal PLABSI events were reported during 142, 240 peripheral line-days (0.67 per 1000 peripheral line-days). Over time, a significant decrease in quarterly risk for neonatal CLABSI events was observed (risk ratio (RR): 0.98; 95% confidence interval: 0.97–0.99; P  = 0.023) and this reduction was significant for the 751–1000 g birth weight cohort (RR: 0.97; P  = 0.015). Most frequently, coagulase-negative Staphylococcus spp. (24.2%) and Staphylococcus aureus (16.1%) were responsible for CLABSI events. A significant reduction in Gram-negative neonatal infections was observed (annual RR: 0.85; P  < 0.001). Conclusion: CLABSI rates in neonatal and paediatric ICUs in our region are low, and neonatal infections have significantly diminished over time. Evaluation of infection prevention programmes is required to determine whether specific strategies can be implemented to further reduce infection risk.